Brown and beige adipose tissue: a novel therapeutic strategy for obesity and type 2 diabetes mellitus. (1st January 2021) - Cheng, Long; Wang, Jingkang; Dai, Hongyu; Duan, Yuhui; An, Yongcheng; Shi, Lu; Lv, Yinglan; Li, Huimin; Wang, Chen; Ma, Quantao; Li, Yaqi; Li, Pengfei; et al.
ABSTRACT: Mammalian adipose tissue can be divided into two major types, namely, white adipose tissue (WAT) and brown adipose tissue (BAT). According to classical view, the main function of WAT is to store excess energy in the form of triglycerides, while BAT is a thermogenic tissue that acts a pivotal part in maintaining the core body temperature. White adipocytes display high plasticity and can transdifferentiate into beige adipocytes which have many similar morphological and functional properties with brown adipocytes under the stimulations of exercise, cold exposure and other factors. This phenomenon is also known as 'browning of WAT'. In addition to transdifferentiation, beige adipocytes can also come from de novo differentiation from tissue-resident progenitors. Activating BAT and inducing browning of WAT can accelerate the intake of glycolipids and reduce the insulin secretion requirement, which may be a new strategy to improve glycolipids metabolism and insulin resistance of obese and type 2 diabetes mellitus (T2DM) patients. This review mainly discusses the significance of brown and beige adipose tissues in the treatment of obesity and T2DM, and focuses on the effect of the browning agent on obesity and T2DM, which provides a brand-new theoretical reference for the prevention and treatment of obesity and T2DM. Graphical Abstract: uf0001